Implementation of Integrated Reporting <IR> Framework In Non-Profit Organization - Nurhaliva, Nurhaliva; Handajani , Lilik; Sokarina , Ayudia (Journal Research of Social Science, Economics, and Management, 2022)
This study aims to implement the 2021 revision of IIRF in X non-profit organization. This research is qualitative research with an action research approach. The results of this study indicate that X non-profit organization is able to present <IR> based on the eight content elements of IIRF, although the information presented in <IR> is not fully presented in full because the adoption of directed <IR> in IIRF is still at an early stage. However, if the organization is consistent with presenting <IR>, there will be a gradual increase in the following years. This research is expected to provide additional guidance on how to apply IIRF as a guide for presenting <IR> for organization X and other non-profit organizations interested in implementing IIRF.